Intellectual capital of the participants in the educational process as a condition for improving the image of a general secondary education institution - Tarasenko, I. (Problems of Engineer-Pedagogical Education, 2020)
The article deals with the concept of intellectual capital of the participants in the educational process in the context of improving the image of an institution of general secondary education. The paper analyses scientific articles dedicated to the question of creating the image of education institutions and intellectual capital of organisations and establishments in this sphere. The conditions for improving the image of a general secondary education institution include the personal image of its headmaster, intellectual capital of the participants in the educational process, social and psychological ambiance of the work environment, exterior of the education institution, etc. The paper classifies and characterises components of the intellectual capital of a general secondary education institution, which include intellectual property, qualification potential of its teachers, information and methodological support, opportunities for professional development, cooperative communication and educational achievements of the recipients of education. The article places special emphasis on the fact that the question of defining the structure and especially the importance of the intellectual capital of an institution of general secondary education for improving its image has attracted insufficient scientific attention. The dependence of the image index of a general secondary education institution on the index of the intellectual capital of its participants (pedagogical personnel and students) is substantiated. In particular, the paper highlights the results of the research which required using the methods of questioning, documentary analysis, indicator evaluation of the intellectual capital of general secondary education institutions, observation, etc. The survey took into account the opinion on the education institution image expressed by members of the public and state administration of education, which since 2015 has been represented in Kharkiv by the Kharkiv City Parent Council. The essence of the intellectual capital of the participants in the educational process is defined as one of the conditions for improving the image of a general secondary education institution. The factorial and criterion model of assessing the level of the intellectual capital of the educational process participants has been developed and substantiated to be used by the heads of general secondary education institutions. The paper highlights that the criteria given in the model should be assessed using different methods such as interviewing, questioning, expert evaluation, etc. Particular attention is drawn to the fact that the model can be used by school principals for evaluating and, subsequently, supporting and developing the intellectual capital of the participants in the educational process, which will significantly affect the internal quality assurance of educational services.